DETERMINAN AKUNTABILITAS KINERJA PEMERINTAH DI KABUPATEN LOMBOK BARAT - Andi Permana Putra; Akram Akram; Hermanto Hermanto (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2018)
The purpose of this study is to analyze and prove the factors that affect the accountability of government performance in financial management, especially in West Lombok regency. Issues of accountability are phenomena and have always been the spotlight in the community, especially the low quality of government agencies' performance in managing local finances that often have an impact on the abuse of authority. Factors that degrade the quality of accountability to the local government is the lack of budget targeting and reporting. Besides it is still less than optimal implementation of performance-based budgeting and internal controls over financial management. This research is an explanatory research. The data in this study are primary data collected using questionnaires. The total sample is 87 regional finance management officials determined using disproportional stratified random sampling technique. Data analysis used in this research is multiple linear regression analysis. This study proves that the implementation of performance-based budgeting, internal control, clarity of budget targets and reporting have a positive effect on the performance accountability of local government financial management.